Neuroendocrine Tumor in a Routine Cervix Cytology - Tavares, Vanessa; Trancas, C; Santos, S (Citotech Online - Case Review, 2020)
Neuroendocrine tumors of the cervix are extremely rare, so their diagnosis is difficult and sometimes confused with some other neoplastic entities. We present a case of a 43-year-old woman with complaints of uterine bleeding and fibroids, proposed for an elective hysterectomy, diagnosed in routine preoperative cytology, as Adenocarcinoma with no other specification. After a colpocytology with biopsy, a cervix neuroendocrine carcinoma was diagnosed, using complementary immunohystochemistry techniques. The patient experienced several treatments, having died about one year later, with metastatic disease.